(3GdJfbjM aj TQM GdhSjWs - (3jMji Hf TQa Hf eQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf, (B676 (3g` s; (3GdZRGdj , MLI GdESdGe CHh MGeO eMeO Hf eMeO GdZRGdj GdTGaYj GdWhSj, MLI GdGSdGe GdZRGdj,J (B505 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf GdETJZGd HGdYde CaVd GdobQH hCLd GdWGYGJ hef CMSfgG LeYkG hJQJjHkG GdhSjW ddEeGe CHj MGeO eMeO Hf eMeO Hf eMeO GdZRGdj s
(3BNQgG (B:s
(3hCeG bhdg hGdhGTQg hGdeSJhTQI aZQjH PcQg CHhYHjO aj ZQjH GdMOjK HZjQ ESfGO gPG BNQ eG hLOfG ef gPG GdTQM hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdTGaYjs